Impact of Global Enrollment on Race, Ethnicity, and Age Representation in Pivotal Gynecologic Cancer Trials Leading to US Food and Drug Administration Drug Approvals - Maheen H. Khan; Kristen R. Ibanez; Courtney Bowen; Duncan Donohue; Ann Oluloro; Elizabeth M. Swisher; Jung-Min Lee (JCO Global Oncology)
PURPOSETo evaluate the impact of international enrollment in landmark gynecologic cancer (Gyn-Ca) trials that supported the US Food and Drug Administration (FDA) drug approvals.METHODSWe examined the FDA drug approval database for approved Gyn-Ca agents between January 2014 and June 2024. We then extracted clinical trial identifiers supporting these approvals using FDA safety labels. Expected enrollment was calculated using gynecologic disease site incidence data from the US Cancer Statistics Program and compared with actual trial enrollment reported on ClinicalTrials.gov.RESULTSFrom 2014 to 2024, 30 Gyn-Ca trials supporting 28 FDA approvals were conducted in US/international (86.7%), international-only (10%), and US-only sites (3.3%) and enrolled 15,294 patients, with 14,053 remaining (74.0% White, 4.1% Black, 12.7% Asian, 8.7% other) after screening for trials not reporting race. Black (–11.0%; P < .0001), Hispanic/Latino (–3.5%; P < .0001), and elderly (–12.6%; P < .0001) participants were under-represented, whereas Asians (+6.8%; P < .0001) were over-represented. Asian (18.3% v 3.5% in trials with or without East Asian sites; odds ratio [OR], 6.19 [95% CI, 5.29 to 7.25]; P < .0001) and Hispanic/Latino (18.6% v 4.6% in trials with or without South American sites; OR, 4.75 [95% CI, 4.00 to 5.63]; P < .0001) enrollment was higher in trials that included East Asian and South American sites, respectively. Black enrollment did not improve despite trials including recruitment in Africa (3.2% v 4.1% Black enrollment in trials with or without African sites; OR, 0.83 [95% CI, 0.38 to 1.83]; P = .53).CONCLUSIONBlack, Hispanic/Latino, and elderly patients were under-represented in pivotal Gyn-Ca trials, whereas Asian patients were over-represented, compared with expected enrollment proportions. Postmarketing studies on under-represented groups should be considered to assess drug efficacy and safety in these populations.